An Autonomous Underwater Vehicle Simulation Using Linear Quadratic Servo Based on Open Control Platform. (13th September 2012) - Syahroni, Nanang; Choi, Jae Weon
Abstract : This paper presents an optimal regulator for depth control simulation of an autonomous underwater vehicle (AUV) using a new approach of decentralized system environment called open control platform (OCP). Simulation results are presented to demonstrate performance of the proposed method.